Current Role of Surgery in the Treatment of Neurocysticercosis - Hamamoto Filho, Pedro Tadao [UNESP]; Norcia, Luiz Fernando [UNESP]; Fleury, Agnès; Zanini, Marco Antônio [UNESP] (My University, 2024)
Neurocysticercosis (NCC) is a common parasitic disease of the central nervous system (CNS) in low- and middle-income countries. The infection is pleomorphic, caused by the larval form of the cestode, Taenia solium, and part of the heterogeneity of its clinical presentations is associated with the localization of the parasite within the CNS. Changes in the current epidemiological trends of NCC indicate that extra-parenchymal NCC is proportionally becoming more frequent. Extraparenchymal NCC is commonly accompanied by raised intracranial hypertension due to hydrocephalus, which is an emergency requiring cyst extirpation by surgical intervention to relieve the symptoms. Although less frequent, parenchymal cysts may also reach giant sizes requiring urgent surgical treatment. Finally, there is an advancement in the comprehension of the association between NCC and epilepsy—and patients with drug-resistant seizures are candidates for surgical treatment. In this narrative review, we summarize the present state of knowledge to update the current trends in the role of surgery in the treatment of NCC.
Keywords: epilepsy; hydrocephalus; inflammation; intracranial pressure; neuro-endoscopy; neurocysticercosis; VP shunt